The Analysis of Signs in the Film Everything Everywhere All at Once by The Daniels - Vania, Rae Tisha; Grahita, Banung (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Everything Everywhere All at Once is considered one of the best films in 2022, as it has received 7 Academy Awards 2023 in the United States, including the prestigious Oscar categories of Best Picture, Actor in a Leading Role, Actress in a Leading Role, Actor in a Supporting Role, Actress in a Supporting Role, Directing, Writing (Original Screenplay), and Film Editing. In this film, we can observe intriguing symbols such as googly eyes and recurring appearances of bagels. The purpose of this research is to explore the elements of representamen/sign, object, and interpretant/interpretation using Charles Sanders Pierce's Semiotics Theory.